PROFIL PEMBELAJARAN TERPADU PADA MATA PELAJARAN IPA DI SEKOLAH MENENGAH PERTAMA - Soesy Sri Wulandari; Prabowo ZA; Imam Supardi (Universitas Jember, 2020)
This study aimed to determine about the integrated learning profile in science subjects in junior high school. The thing that will be analyzed is how to process the integrated learning planning in science subjects in junior high school. The data collection is described and analyzed through the reduction and examination process which validity used triangulation method. The descriptive analysis results found the answers to research questions. Then, the researchers drew a conclusion from the results of research.The results of the study found that teachers did not apply integrated learning that involves cognitive, affective, and psychomotor aspects. Based on these findings, it can be concluded that the integrated learning profile in science subjects in junior high school do not equivalent to the characteristics of integrated learning. The main cause of the condition is that teachers did not understand the characteristics of integrated learning in science subjects.